Procedure for Making Snap On Smiles Using Acetyl Thermoplastic Resin Materials to Improve Aesthetics in Upper Anterior Teeth - Isma Suprapti; Sulfiani; Magfira; Andi Meinar Dwi Rantisari Thayeb (CV. Eureka Murakabi Abadi, 2023)
Snap on smile is a denture prosthesis made using high-tech dental resin, namely acetyl thermoplastic resin. Acetyl thermoplastic is a thermoplastic material, rigid, and not easily broken. This study aims to find out how the procedure for making a snap on smile with acetyl thermoplastic material can improve aesthetics and function in aesthetic cases of upper anterior teeth. This study uses a descriptive method that will describe the procedure for making a snap on smile using acetyl thermoplastic resin to improve the esthetics of the upper anterior teeth. The procedure for making a snap on starts with the acceptance of the model, duplicating the working model, fixing the working model, implanting it in the ocludator, waxing up, flasking the top cuvette, installing sprue, flesking the top cuvette, boiling out, preheating, injecting, deflasing, sprue cutting, fitting, finishing and polishing. The conclusion of this study is the snap on smile on prosthesis that is made without tooth preparation or reduction of the teeth and without the use of cementation on the teeth or glue and can also be removed by the patient.